Implementasi Model Discovery Learning melalui Pembelajaran Berdiferensiasi untuk Meningkatkan Kolaborasi Pelajaran Matematika Kelas 1 SD - Marwiyah Marwiyah; Krisma Widi Wardani (FARABI: Jurnal Matematika dan Pendidikan Matematika, 2024)
Action research was conducted in Class I of RA Kartini 01 Public Elementary School Gendongan 01, focusing on implementing a differentiated learning model to enhance students' collaboration skills and learning outcomes. This study comprised two cycles of action research. Data were collected through teacher observation sheets during the implementation of the discovery learning model with a differentiated approach, as well as through student learning outcome observation sheets in the form of post-tests. The results indicated a significant improvement in students' collaboration skills from the pre-cycle to Cycle II. In the pre-cycle, only 2 students (7.41%) were categorized as highly capable (81-100). This number increased to 5 students (19.23%) in Cycle I and 10 students (38.46%) in Cycle II. The capable category (61-80) also showed improvement from 4 students (14.81%) in the pre-cycle to 7 students (26.92%) in Cycle I and 11 students (42.31%) in Cycle II. Students in the less capable (21-40) and incapable (0-20) categories drastically decreased from 19 students (70.37%) in the pre-cycle to 8 students (30.77%) in Cycle I and no students (0%) in Cycle II. There was also a significant improvement in learning outcomes, with students in the highly capable category (81-100) increasing from 12 students (44.40%) in the pre-cycle to 16 students (59.30%) in Cycle I and 19 students (70.40%) in Cycle II. There were no students categorized as less capable (21-40) or incapable (0-20) in Cycles I and II. Therefore, the implementation of a differentiated learning model has proven effective in enhancing students' collaboration skills and academic achievement.